Ten-Year Trends in Self-Reported Family and Psychological Problems among Swedish Adolescents - Ybrandt, Helene (European Journal of Mental Health, 2014)
The aim of the study was to compare problem severity among Swedish adolescents, using self-reported and interviewer-rated data from 2000 and 2010, gathered with the Adolescent Drug Abuse Diagnosis (ADAD) interview. Data relating to family relationships, psychological status and problems were collected in two samples randomly selected from the adolescent population aged 15–17 years (121 adolescents in the year 2000 and 485 adolescents in the year 2010). The results show that the self-rated and interviewer-rated problem severity of adolescents in 2000 and in 2010 seems to be unchanged, with no increased polarisation for sex and socio-economic groups. There was a difference, however, was of girls reporting more severe problems in family relationships compared to boys. In 2010, compared to 2000, adolescents reported on fewer psychological problems (e.g. experiences of serious anxiety and tension, comprehension and concentration disorder, memory loss and, in addition, with relationships in and outside the family sphere – e.g. problems with getting along with siblings, and with trusting other people). In order to promote the mental health of adolescents it is essential during the next decade to reveal relationship problems, such as problems of insecurity with people outside the family.